2005
DOI: 10.1111/j.1366-9516.2005.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and comparative ecology of testate amoebae inhabitingSphagnum‐dominated peatlands in the Great Lakes and Rocky Mountain regions of North America

Abstract: Testate amoebae (Protozoa: Rhizopoda) are common inhabitants of peatlands. Strong relationships between community composition and substrate moisture in Sphagnum‐dominated peatlands have made them particularly useful as hydrological proxies in environmental and palaeoenvironmental research. However, stability of these relationships in geographical space is important for widespread applicability. In this study, we compared testate amoeba communities inhabiting Sphagnum‐dominated peatlands of the Great Lakes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 44 publications
(83 reference statements)
2
43
0
2
Order By: Relevance
“…Direct comparison among studies is difficult because most studies have used one-time DWT measurement, with the notable exception of Woodland et al (1998). To date, only one study has compared two sites using exactly the same methods (Booth and Zygmunt, 2005). But in this study, too, the DWT measurements were not done on the same day, and even had they been given the distance among sites (Rocky Mountains and Great Lakes regions, respectively) the sampling date would be less important than the time since the last significant rain event.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct comparison among studies is difficult because most studies have used one-time DWT measurement, with the notable exception of Woodland et al (1998). To date, only one study has compared two sites using exactly the same methods (Booth and Zygmunt, 2005). But in this study, too, the DWT measurements were not done on the same day, and even had they been given the distance among sites (Rocky Mountains and Great Lakes regions, respectively) the sampling date would be less important than the time since the last significant rain event.…”
Section: Discussionmentioning
confidence: 99%
“…Given the above-mentioned methodological differences in water-table depth measurements, it is difficult to compare species optima with previous results, as most studies have only measured DWT on a single sampling occasion and therefore do not take account of annual variations in water-table. Booth and Zygmunt (2005) compared the DWT optima for testate amoebae between two distant study sites in North America. They found that although the communities were sometimes quite different, the species' optima were consistent between the two regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrological preferences of many taxa are well known and appear consistent across broad geographic regions (Booth and Zygmunt 2005). However, there are notable differences in community composition between studies, and there are several important taxa whose hydrological preferences are still inadequately understood.…”
Section: Introductionmentioning
confidence: 99%
“…Testate amoebaebased hydrological transfer functions have been developed in many parts of the world; Alaska (Markel et al, 2010;Payne et al, 2006), Canada (Charman and Warner, 1997;Warner and Charman, 1994), Europe , Greece (Payne and Mitchell, 2007), New Zealand (Charman, 1997;Wilmshurst et al, 2003), North America (Booth, 2008;Booth and Zygmunt, 2005), Northern Ireland ), Switzerland (Mitchell et al, 1999), Poland (Lamentowicz et al, 2008;Lamentowicz and Mitchell, 2005), and the United Kingdom (Woodland et al, 1998). Due to spatial autocorrelation (Borcard et al, 1992;Lennon, 2000), transfer functions require validation against data sets that are completely independent of the training set (Belyea, 2007;Birks et al, 2010).…”
Section: Introductionmentioning
confidence: 99%